Analytical method development and validation for simultaneous estimation of mefloquine hydrochloride and artemether in bulk drug by simultaneous equation method - Choudhary, Amit; Sinha, Manish; Amar Deep Ankalgi; Goyal, Kamya; Devi, Arti (Journal of Applied Pharmaceutical Research, 2020)
The purpose of the research is to establish a fast, accurate, precise, and low-cost UV-Visible spectrophotometry method for the quantitative simultaneous estimation of mefloquine hydrochloride and artemether in bulk drug. The UV-Visible method employed was a simultaneous equation method. Ethanol was used as a solvent and therefore the absorption maxima (λ max) was found to be 229 nm and 209 nm for mefloquine hydrochloride and artemether. The linearity ranges of both drugs were 1-6 μg/mL and 100 – 350 μg/mL with a regression coefficient r2 ≥ 0.998 respectively. The method was validated for different parameters according to International Conference on Harmonization ICH Q2B guidelines. The average recovery for mefloquine hydrochloride was found to be 100 per cent and artemether 99.3 per cent. The method was also found precise and robust with a per cent relative standard deviation of less than 2. All the parameters result obtained within the limits. Therefore, the proposed method for the accurate quantitation of mefloquine hydrochloride and artemether in the bulk drug was successfully implemented.